Summary of CPWF Research in the Volta River Basin - CGIAR Challenge Program on Water and Food (2013)
The farmers in the Volta river basin, some of the poorest in the world, generally rely on rain-fed agriculture. However, insufficient or irregular rainfall frequently puts farmers at risk of losing their crops. In addition, climate change is making already variable rainfall less reliable. The risk of losing crops makes farmers reluctant to invest in agriculture and water management. Farmers must have access to a reliable water supply to sustain their livelihoods.